Subversive Semantics in Political and Cultural Discourse The Production of Popular Knowledge - Mackenthun, Gesa; Dosch, Jörn (Edition Politik, 2023)
The large-scale use of semantic transfer and inversion as rhetorical tactics is particularly prevalent in right-wing discourses and populist »alternative knowledge« production. The contributors to this volume analyze processes of re-semanticizing received meanings, effectually re-coding those meanings. They investigate to what extent rhetorical maneuvers serve to establish new and powerful belief systems beyond rational and democratic control. In addition to the contemporary rightwing and conspiracy narratives, the contributions examine the discursive fields around conceptions of human nature and the deep past, population politics, gender conceptions, use of land, identity politics, nationhood, and cultural heritage.